Chebulagic acid targets FBXO38 to enhance natural killer cell-mediated anti-tumor immunity in lung adenocarcinoma - Xiwen Hu; Rui Sha; Feiran Yang; Jinwen Chai; Bin Liu; Xiaoqing Xu (Human Cell, 2026)

Activation of the circAGFG1/miR-195-5p/PD-L1 axis induces lung injury in sepsis - Yang Bi; Rui Ding; Xinyan Liu; Yun He; Xukun Liu; Shouye Ma; Chaofan Wang; Zhongfa Zhang; Xuan Song (Human Cell, 2025)
Severe sepsis can escalate to acute lung injury (ALI), a critical condition with limited treatment options. Emerging research highlights the role of non-coding RNAs, including microRNAs (miRNAs) and circular RNAs (circRNAs), in regulating epithelial and immune cell responses in sepsis-induced ALI. This study delves into the circAGFG1/miR-195-5p/PD-L1 axis to elucidate its potential in this context. The conducted experiments using Th17 cells differentiated from CD4+ T cells isolated from human umbilical cord blood, co-cultured with transfected Calu-3 cells. The assessed cell viability, RNA, and protein expression levels under inflammatory stimuli. In addition, we collected bronchoalveolar lavage fluid and lung tissues from a cecal ligation and puncture mouse model. Quantification of RNA and protein expression of inflammatory and survival markers provided insights into the regulatory mechanisms involved. Peripheral blood samples from sepsis/ALI patients and healthy controls revealed that circAGFG1 expression is significantly downregulated, while miR-195-5p expression is upregulated in patients compared to healthy individuals. In both Calu-3 cells and induced Th17 cells, as well as in sepsis-induced ALI mouse models, the circAGFG1/miR-195-5p/PD-L1 axis was shown to regulate the expression of inflammatory cytokines, Th17 cell differentiation, and markers of epithelial cell survival. Results show the circAGFG1/miR-195-5p/PD-L1 axis plays a critical role in the pathogenesis of sepsis-induced ALI. Targeting this axis could present a novel therapeutic strategy for preventing ALI in sepsis and other conditions characterized by heightened lung inflammation. This research paves the way for new treatment approaches, offering hope for improved outcomes in patients suffering from severe sepsis and ALI. Graphical abstract

LncRNA OLMALINC promotes osteosarcoma progression through USP1-mediated autophagy suppression - Jianping Li; Bo Yu; Zhaowen Xue; Yiping Liang; Shanchuang Chen; Tao Gui; Zitao Liu; Lei Zhang; Rui Peng (Human Cell, 2025)

ZC3H13 promotes autophagy in bladder cancer through m6A methylation modification of PJA2 and ubiquitination of KSR1 - Beibei Liu; Mengjie Chen; Yujie Liang; Zhijie Mei; Wei Sun; Wuyue Gao; Tiantian Zhang; Rui Wang; Yuanyuan Guo (Human Cell, 2024)

F-box and leucine-rich repeat protein 16 controls tamoxifen sensitivity via regulation of mitochondrial respiration in estrogen receptor-positive breast cancer cells - Feng Chen; Lu Wang; Yanrong Feng; Wenxin Ma; Junqin Liu; Qianyao Bi; Yao Song; Rui Gao; Yanhan Jia (Human Cell, 2023)

Novel insights into tumorigenesis and prognosis of endometrial cancer through systematic investigation and validation on mitophagy-related signature - Rui Sun; Xiaoyu Zhou; Tong Wang; Yao Liu; Lina Wei; Ziyi Qiu; Chunping Qiu; Jie Jiang (Human Cell, 2023)

ZNRF2 as an oncogene is transcriptionally regulated by CREB1 in breast cancer models - Jin-Tao Liu; Zhen-Xuan Sun; Rui Zhong; Yi-Dan Zhang; Teng Wang; Yu-Dong Hou; Jian-Heng Bao; Lei Zhang; Bo Chen (Human Cell, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Activating transcription factor 3 is a potential target and a new biomarker for the prognosis of atherosclerosis - Weiwei Qin; Huiyu Yang; Gaizhen Liu; Rui bai; Yunfei Bian; Zhiming Yang; Chuanshi Xiao (Human Cell, 2021)

SNHG16 regulates invasion and migration of bladder cancer through induction of epithelial-to-mesenchymal transition - Wenwei Chen; Tao Jiang; Houping Mao; Rui Gao; Hua Zhang; Yanfeng He; Changyi Liu; Qin Chen (Human Cell, 2020)

Inhibition of two gastric cancer cell lines induced by fucoxanthin involves downregulation of Mcl-1 and STAT3 - Rui-xue Yu; Rui-tao Yu; Zhong Liu (Human Cell, 2018)

Erratum to: Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)